Dynamic Associations of Change in Physical Activity and Change in Cognitive Function: Coordinated Analyses of Four Longitudinal Studies - Magnus Lindwall; Cynthia R. Cimino; Laura E. Gibbons; Meghan B. Mitchell; Andreana Benitez; Cassandra L. Brown; Robert F. Kennison; Steven D. Shirk; Alireza Atri; Annie Robitaille; Stuart W. S. MacDonald; Elizabeth M. Zelinski; et al. (Journal of Aging Research, 2012)
The present study used a coordinated analyses approach to examine the association of physical activity and cognitive change in four longitudinal studies. A series of multilevel growth models with physical activity included both as a fixed (between-person) and time-varying (within-person) predictor of four domains of cognitive function (reasoning, memory, fluency, and semantic knowledge) was used. Baseline physical activity predicted fluency, reasoning and memory in two studies. However, there was a consistent pattern of positive relationships between time-specific changes in physical activity and time-specific changes in cognition, controlling for expected linear trajectories over time, across all four studies. This pattern was most evident for the domains of reasoning and fluency.